Relationship of Nurse Caring Behavior With Level Parents' Anxiety in Infusion Installation Child in Theresia Room of Santa Hospital Elisabeth Batam City In 2022 - friska Ginting; Mestiana Br Karo; Septa Ginting (LLDIKTI Wilayah 1, 2023)
Anxiety is a response experienced by every human being to a certain situation such as anger, sadness, fear, pain with a combination of phenomenological and physiological qualities. Infusion is an action taken to provide fluids into the body. Caring behavior is a form of basic nursing practice that appears with an attitude of patience, honesty, confidence, presence, touch, compassion and humility in carrying out actions so that the patient's healing process is faster. Objective: The purpose of this study was to identify the relationship between the caring behavior of nurses and the level of parental anxiety in infusion in children in the Theresia room, Santa Elisabeth Hospital, Batam City in 2022. Methods: The research design used is a correlational study with a cross sectional approach. The population in this study were parents whose children were treated in Theresia's room in January 2022 with the inclusion criteria of parents whose children were given intravenous infusion for the first time and were under 12 years of age and obtained a sample of 32 respondents. Sampling with total sampling. Results: The results of the study using the Spearman Rank test, namely p value = 0.039 (p <0.05) and rho (r) = -0.366, it can be concluded that there is a relationship between the caring behavior of nurses and the level of anxiety of parents in infusion in children in the Theresia room at the Santa Elisabeth Hospital. Batam city in 2022.